Dissociative Symptoms in Bipolar Disorder: Impact on Clinical Course and Treatment Response - Steardo, Luca; Carbone, Elvira Anna; Ventura, Enrica; de Filippis, Renato; Luciano, Mario; Segura-Garcia, Cristina; De Fazio, Pasquale (Frontiers in Psychiatry, 2021)
Background: Dissociative symptoms are under recognized and scarcely studied by clinicians and researchers in patients with bipolar disorder (BD). We examined the relationship between dissociative symptoms and the psychotic features in patients with BD and assessed clinical and socio-demographic characteristics more frequently associated with dissociative symptoms and treatment response. Methods: Participants were 100 adult outpatients with BD. They were screened with semi-structured interview to collect socio-demographic and clinical characteristics; the Dissociative Experiences Scale-II (DES-II) and the ALDA scale were used to assess dissociative psychopathologies and response to treatment with mood stabilizers respectively. Results: DES score (mean 31,7±21,7) correlated with clinical variables, BD features and course of illness. Psychotic symptoms, mixed features and previous suicide attempts significantly predicted DES score (F(3, 47) = 39.880, p < .001, R2 corrected = .713). Dissociative symptoms were inversely correlated with poor response to treatment (r=-.593; p < .001). Limitations: Cross-sectional design with a small sample and backward clinical assessment of psychotic symptoms. Conclusions: Dissociative phenomena are closely related to the presence of psychotic symptoms, mixed features and previous suicide attempts in BD, especially in BD-I. Given the close association between dissociative and psychotic symptoms, this association could represent a diagnostic indicator of BD-I that may guide the clinician to plan the most appropriate treatment.